Associations between respiratory illnesses and secondhand smoke exposure in flight attendants: A cross-sectional analysis of the Flight Attendant Medical Research Institute Survey - Redberg Rita F; Haight Thaddeus J; Beatty Alexis L (BMC, 2011)
Abstract Background Secondhand tobacco smoke (SHS) is associated with increased risk of respiratory illness, cancer, and cardiovascular disease. Prior to smoking bans on airlines in the late 1980s, flight attendants were exposed to a significant amount of SHS. In the present study, we examine associations between flight attendant SHS exposure and development of respiratory illnesses and cardiovascular disease. Methods Between December 2006 and October 2010, three hundred sixty-two flight attendants completed an online questionnaire with information regarding experience as a flight attendant, medical history, smoking history, and SHS exposure. Rates of illnesses in flight attendants were compared with an age and smoking history matched population sample from NHANES 2005-2006. Logistic regression analysis was used to examine the association of reported medical conditions and pre-ban years of exposure. Results Compared with the sample from NHANES 2005-2006, flight attendants had increased prevalence of chronic bronchitis (11.7% vs. 7.2%, p < 0.05), emphysema/COPD (3.2% vs. 0.9%, p < 0.03), and sinus problems (31.5% vs. 20.9%, p < 0.002), despite a lower prevalence of medical illnesses including high blood pressure, diabetes, high cholesterol, heart failure, cancer, and thyroid disease. Amongst flight attendants who reported never smoking over their lifetimes, there was not a significant association between years of service as a flight attendant in the pre-smoking ban era and illnesses. However, in this same group, there was a significantly increased risk of daily symptoms (vs. no symptoms) of nasal congestion, throat, or eye irritation per 10-year increase of years of service as a flight attendant prior to the smoking ban (OR 2.14, 95% CI 1.41 - 3.24). Conclusions Flight attendants experience increased rates of respiratory illnesses compared to a population sample. The frequency of symptoms of nasal congestion, throat or eye irritation is associated with occupational SHS exposure in the pre-smoking ban era.